Effects of religiosity, spirituality, and personal values on employee performance: a conceptual analysis - Osman-Gani, Aahad M.; Hashim, Junaidah; Ismail, Yusof (2010)
This paper presents a conceptual analysis of the effects of religiosity, spirituality, individual values on employee performance in organizations while it highlights the moderating and mediating effects of individual values and organizational commitment. This paper developed some propositions that could be tested through empirical research in future. Based on a conceptual framework that is presented to guide future research, the implications for professional practice are discussed.